AN ALTERNATIVE MODEL FOR OPTIMISING PAYLOADS OF BUILDING GLASS - Taha, H.A. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: This article deals with the development of a multi-stage model for optimising payload placement on a hauler-trailer rig in an environment described by physical and regulatory constraints. The model which purports to be an improvement on an earlier model provides two types of solution i.e. a feasible solution which satisfies all zone loading and axle weight constraints, or an infeasible solution giving the cause and quantification of source(s) of infeasibility which may be used to modify model inputs for further attempts at optimisation. AFRIKAANSE OPSOMMING: Die artikel handel oor die ontwikkeling van 'n multistadiummodel vir die optimisering van vragplasing op 'n sleepwa onder fisiese en regsvoorskriftelike voorwaardes. Die model wat daarop aanspraak maak dat dit 'n verbetering is op 'n vorige model, lewer as uitset twee oplossingstipes naamlik 'n gangbare oplossing wat alle sone- en aslasrandvoorwaardes eerbiedig, of 'n ongangbare oplossing wat oorsaak en kwantifisering van ongangbaarheidsbronne uitwys vir die gebruik van gewysigde modelinsette by verdere pogings tot optimisering.